Political leaders and the local constitution - Karlsson, David; Erikson, Malgorzata (Scandinavian Journal of Public Administration, 2013)
The relation between institutions and political leadership has been the central theme of the research project “Local political leadership in a time of constitutional transition” at the School of Public Administration, University of Gothenburg. The project, which started in 2006 was funded by the Swedish Research Council and led by Professor Henry Bäck. Results from the project have contributed with new knowledge in the field of local political leadership in a number of aspects. This special issue of Scandinavian Journal of Public Administration marks the end of this project. Each of the three included articles represents essential aspects of how political institutions affect local political leadership. The first article has been written within the project, while the two others are written by internationally renowned local government scholars and provide comparative perspectives on the importance of institutions for political leadership.